Labor relations conflict in China: An analysis of conflict measure, conflict solution and conflict outcomes. Issue 17 (25th September 2022) - Xi, Meng; Zhou, Lulu; Zhang, Xufan; Zhao, Shuming
Abstract: Conflict is inevitable and an essential part of organizational life, as the goals of employers and employees are often incompatible. In this study, by employing both qualitative and quantitative methods, we inductively identified the categories of labor relations conflicts (interest-based, rights-based, and affect-based conflicts) and developed a three-dimensional scale that reflects employees' perceptions of labor relations conflicts in the Chinese context. By using matched data from 1223 employees and 136 human resource (HR) managers and employing hierarchical linear modeling (HLM) analysis, we tested the hypotheses and examined the effectiveness of partnership practices on reducing labor relations conflicts, the negative effects of labor relations conflicts on employees' attitudes and behaviors, and the mediating role of labor relations conflicts on the relationship between partnership practices and employees' attitudes and behaviors. The theoretical contributions and practical implications of the findings are discussed.